Correction: Anisotropy of CoII transferred to the Cr7Co polymetallic cluster via strong exchange interactions. Issue 14 (23rd March 2018) - Garlatti, Elena; Guidi, Tatiana; Chiesa, Alessandro; Ansbro, Simon; Baker, Michael L.; Ollivier, Jacques; Mutka, Hannu; Timco, Grigore A.; Vitorica-Yrezabal, Inigo; Pavarini, Eva; Santini, Paolo; Amoretti, Giuseppe; et al.
Abstract : Correction for 'Anisotropy of Co II transferred to the Cr7 Co polymetallic cluster via strong exchange interactions' by Elena Garlatti et al., Chem. Sci., 2018, DOI: ;10.1039/c8sc00163d .